Re-telling: A Narrative inquiry of Indonesian graduate students’ speaking experiences in a United Kingdom university - Abrar, Mukhlash (Universitas Pendidikan Indonesia, 2019)
The purpose of this inquiry is to explore and make sense of the stories of Indonesian graduate students’ speaking experiences in the academic settings during their study in a United Kingdom university. More specifically, the study is intended to understand their speaking challenges and strategies to overcome the challenges both in classroom and university-surrounding settings. To achieve the purpose of the study, narrative inquiry is employed. Two Indonesian graduate students participated in this study and shared the experiences before and after coming to study in the university. The findings of this narrative inquiry indicate that language-related issues, individual factors, and cultural differences hinder the participants from actively being involved in the verbal communication. To cope with the challenges, the participants applied communication strategies by asking for clarification and repetition. The study suggests that language mastery, including accent, is crucial because it influences the understanding in communication.